2018
DOI: 10.3390/ijerph16010035
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Polish Nurses for Prescribing and the Level of Professional Burnout

Abstract: Those in the medical profession, due to close contact and the emotional commitment of caring for patients, are particularly vulnerable to the occurrence of a phenomenon known as occupational ‘burnout’. The presented work deals with the problem of burnout and its relationship with new tasks undertaken by nurses. The aim of the study was an analysis of the relationship between the level of professional burnout of the nurses examined and their readiness to take on new duties related to writing prescriptions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
3
20
2
2
Order By: Relevance
“…Burnout was higher among young employees. The findings of previous studies confirm this point [11,20,27,40]. Maslach stated that this syndrome is more influential in young professionals who work in high-risk and client-centered fields such as health services [19], and as age increases burnout decreases.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Burnout was higher among young employees. The findings of previous studies confirm this point [11,20,27,40]. Maslach stated that this syndrome is more influential in young professionals who work in high-risk and client-centered fields such as health services [19], and as age increases burnout decreases.…”
Section: Discussionmentioning
confidence: 54%
“…Health worker’ burnout is a considerable challenge for health systems, with potential negative consequences for the health care provider, the patients and the health care organizations [4,5,6,7,8,9]. For this reason, burnout has attracted considerable research attention in the past two decades, in both developing and developed countries [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have not been any other analyses of nurse prescribing in Poland during the implementing period. Some Polish research has reported the positive opinions of nurses about prescribing [20][21][22], but that research did not assess nurse prescribing practice. A better understanding of the determinants of prescribing patterns in Poland may help shape future workforce policy in the medical sector and contribute to the design and implementation of optimal and cost-effective initiatives to improve care quality.…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare settings, burnout negatively impacts outcomes at the individual, interpersonal, and institutional levels. At the individual level, burnout is associated with reduced job satisfaction, increased absenteeism, medical errors, sickness, injury, and accidents among healthcare providers [ 2 , 3 ]. These individual-level impacts may lead to reduced care quality and higher mortality among patients [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%